Kecerdasan Budaya Mahasiswa Pascasarjana Bimbingan dan Konseling Universitas Negeri Padang T.M 2018 - Syarifah Wahidah; Yeni Karneli; Mudjiran Mudjiran (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Life as a member of a multicultural society makes individuals must be smart in interacting with others, especially with different cultures. The purpose of this study was to see how cultural intelligence in the Postgraduate Guidance and Counseling students of the State University of Padang T.M 2018. quantitative research with cross sectional survey methods. Data were analyzed descriptively by dividing into 3 levels: low, medium, and high. And to assess the results of each dimension of cultural intelligence, the mean and percentage are calculated. The results found in the metacognitive category (CQ) obtained an average of 69.18% questionnaire, cognitive category (CQ) 54.53%, motivation category (CQ) 67.20%, and 63.08% behavioral factors overall these dimensions entered into good category. The overall results of the four dimensions obtained an average score of 63.49% with a good category. Which means that the level of cultural intelligence of Postgraduate Guidance and Counseling students at the State University of Padang T.M 2018 are all in the good category. Based on the results of this study it can be concluded that overall the students belong to individuals who have the ability to interact, adjust themselves, understand their abilities when they are in a different cultural situation.